Grado de relación entre autoeficacia y rendimiento académico en una universidad privada (Investigaciones) - Rossi Valverde, Ricardo Manuel (2022)
This work aimed to determine the degree of relationship between self-efficacy and academic performance in a private university. The Specific Perceived Self-Efficacy Scale for Academic Situations was applied to the sample of 414 Administration students, in addition, the grade record was used. The value of 0.945 for Spearman’s rho explains a considerable positive relationship, which supports that 80.2% of the students who perceive a high level of self-efficacy obtained a high academic performance, however, the 1.7% who perceive their self-efficacy in a medium level obtained a low academic performance. Timely intervention would help those students with lower levels of self-efficacy to be guided to achieve good academic performance.